The effects of the omnichannel approach on business sustainability as mediated by customer satisfaction - Bobadilla, Jamie Ann Sze (Animo Repository, 2023)
The COVID-19 pandemic has created a devastating impact on the economy and has caused a tremendous shift in consumer lifestyle. The “new normal” is to purchase needs and wants through e-commerce platforms. However, as the situation gradually normalizes, consumers actively utilize both traditional and online channels in purchasing goods. Thus, this study examines whether or not businesses should adopt an omnichannel strategy, especially in a dynamic business environment. Specifically, this research delves into the effects of the omnichannel approach on business sustainability as mediated by customer satisfaction. A non-probability convenience quota sampling was utilized in gathering responses. Three hundred eighty-five (385) generation Z individuals who live in Manila City and have purchased from a particular brand both through online and offline channels were surveyed. The study concluded that there is a positive relationship and effect between the three variables: Omnichannel Approach, Customer Satisfaction, and Business Sustainability, and that Customer Satisfaction mediates the effect of the Omnichannel Approach on Business Sustainability. Consumers are currently into a seamless shopping experience and prefer businesses who are incorporating sustainability, through the economic, social, and environmental aspects, in their operations. Hence, organizations should implement an omnichannel approach to attain customer satisfaction and achieve business sustainability.